(untitled) (OODBODHAN, 2025)
The modern world has growing demand on light weight vehicle for which fuel efficiency is most important. This has drawn into research on the alternative materials for vehicle suspension system which is crucial in enhancing the efficiency of vehicle. This research presents a finite element analysis of composite leaf spring to evaluate their feasibility as replacement for steel leaf spring. The composite materials considered to carry out this research includes Epoxy/E-Glass, Epoxy/Carbon, and Epoxy/Bamboo. The static structural analysis for these materials is carried out using ANSYS Static Structural domain under various loading condition. The results indicate that composite leaf springs has a 23-26% weight reduction as compared to steel material, improved stress distribution and enhanced vibration damping characteristics. Among the analyzed materials, Epoxy/Carbon shows the highest stiffness and durability that makes this material suitable for light weight vehicle application.